2014
DOI: 10.1093/nar/gku159
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the rules by which dynamics of mRNA secondary structure affect translation efficiency in Saccharomyces cerevisiae

Abstract: Messenger RNA (mRNA) secondary structure decreases the elongation rate, as ribosomes must unwind every structure they encounter during translation. Therefore, the strength of mRNA secondary structure is assumed to be reduced in highly translated mRNAs. However, previous studies in vitro reported a positive correlation between mRNA folding strength and protein abundance. The counterintuitive finding suggests that mRNA secondary structure affects translation efficiency in an undetermined manner. Here, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 58 publications
(67 reference statements)
7
95
2
Order By: Relevance
“…In contrast, translation elongation can be regulated by features contained within the ORF or nascent polypeptide (45,47,48). For example, codon usage (47), RNA structure (59,60), and certain nascent polypeptide sequences can alter the rate of ribosomal transit (45). It will be of interest to identify those features of flaviviral and cellular RNAs that confer a dependency on function of the ribosomal stalk proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, translation elongation can be regulated by features contained within the ORF or nascent polypeptide (45,47,48). For example, codon usage (47), RNA structure (59,60), and certain nascent polypeptide sequences can alter the rate of ribosomal transit (45). It will be of interest to identify those features of flaviviral and cellular RNAs that confer a dependency on function of the ribosomal stalk proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on model oligonucleotides have shown that the presence of RNA secondary structure promotes ribosome pausing (126). However, in vivo, the situation is considerably more complicated, reflecting interplay between multiple parameters, including RNA structure, tRNA abundance, and codon choice (72). One study using in vitro structurome data from yeast (43) and in silicopredicted structures in E. coli proposed that rapid translation of codons associated with highly abundant tRNAs is offset by greater RNA structure associated with these codons, leading to a smoothing of translation rate (31).…”
Section: Stability and Degradationmentioning
confidence: 99%
“…This type of ribosome queuing has been much studied in theoretical approaches [78][79][80][81], and is a complex function of the distribution of codon speeds in different parts of an mRNA. While dense packing of ribosomes generally leads to slower ribosome movement because of collisions, it was also suggested that dense packing can negate the effect of secondary structures which cannot reform between ribosomes that follow each other closely [82].…”
Section: From Trna Selection To Ribosomal Speedmentioning
confidence: 99%